Control of mosquito vectors of tropical infectious diseases: (1) Bioefficacy of mosquito coils containing several pyrethroids and a synergist - Yoshio Katsuda (2018)
The bioefficacy of mosquito coils containing several pyrethroids were tested in a 25 m3 room against Culex pipiens quinquefasciatus, Aedes aegypti and Anopheles dirus. The test results were compared with tests against Culex pipiens pallens in Japan. Based on the KT50 values (the 50% knockdown time) of mosquito coils containing dl, d-T80-allethrin, d, d-T-prallethrin and methoxymethyl-tetrafluorobenzyl tetramethyl- cyclopropanecarboxylate (K-3050) at doses of 0.05-0.5% (w/w) with or without a Synergist, the pyrethroid susceptibility of the four mosquito species was as follows: Cx. p. quinquefasciatus was several times more tolerant to pyrethroids than Cx. p. pallens, Ae. aegypti was a further several times more tolerant than Cx. p. quinquefasciatus, and An. dirus was more susceptible than Cx. p. pallens (KT50 value: about half of Cx. p. pallens). The order of their susceptibilities is common for pyrethroids. Mosquito coils containing d, d-T-prallethrin and K-3050 at doses of 0.05-0.2% (w/w) and N-(2-ethylhexyl) bicycle-[2,2,1]-hept-5-ene-2,3-dicarboxyimide as a synergist at a ratio of 2 times the active ingredient were highly effective against Ae. aegypti, the most important mosquito vector for dengue fever.